Cannabis what teenagers need to know - Mehta, Angeli (United States : BBC Active, 2006)
This program explores how cannabis is affecting young minds, and investigates whether or not there's link between the drug and psychotic illness
Title from title screen
Editor, Mike Robinson ; camera, Will Edwards, Steve Vale ; sound, Tony Pasfield, Chris Gibbions, Michael Williams
Keywords: Cannabis; Drug abuse